Concordance between Isothermal Amplification-Real Time Fluorescence Assay and Reverse Transcriptase Real Time Polymerase Chain Reaction for Detecting SARS-CoV-2 - Irawati, Indri; Turbawaty, Dewi Kartika; Suraya, Nida (Althea Medical Journal, 2024)
Background: There are various nucleic-acid-based diagnostic tests used to detect SARS-CoV-2 in COVID-19 patients such as reverse transcription polymerase chain reaction (RT-PCR) and isothermal amplification real time fluorescence assay (IARTFA), with the first-mentioned is considered as the gold standard. The IARTFA is an alternative method using cross priming amplification (CPA) technique under constant temperature, with a simpler procedure and faster result. This study aimed to determine the concordance between IARTFA and RT-PCR in detecting SARS-CoV-2.Methods: This was an observational cross-sectional study with a random sampling method, conducted from August-October 2021 in Dr. Hasan Sadikin General Hospital, Bandung. Data on patients was obtained from medical records. Cohen's kappa test was used to determine concordance between both methods.Results: A total of 30 subjects were collected, including subjects with positive result on RT-PCR and IARTFA (n=15), negative result on both methods (n=5), and with positive result on RT-PCR but negative on IARTFA (n=10). There were discrepancies between both methods in subjects with cycle threshold (CT) values ≥35. However, there was a significant concordance between both methods (Cohen’s kappa coefficient of 1, p = 0.006).Conclusion: In addition to RT-PCR, IARTFA is an alternative method for detecting SARS-CoV-2 with advantages and excellent concordance. In communicable diseases such as COVID-19, along with healthy lifestyles such as isolation and wearing masks, early diagnosis is important to prevent and manage the spread of the disease.